The Effect of Service Quality, Perceived Value, on Revisit Intention Mediated by Customer Satisfaction in Primary Health Care - Wiogo, Lanny (Dinasti Research, 2025)
The healthcare system in Indonesia plays a vital role in public well-being and is continuously evaluated for improvement. Customer satisfaction is crucial in healthcare, as it directly influences patient retention and revisit intention. This study examines the interplay between service quality, perceived value, patient satisfaction, and revisit intention at Klinik Pratama XYZ, a primary healthcare clinic in Kelapa Gading, North Jakarta. Despite a 5.7% growth in patient visits from 2022 to 2023, this increase fell short of expectations, highlighting the need for service enhancement. The research adopts a quantitative approach to analyze how service quality and perceived value affect patient satisfaction and their subsequent revisit intention. Factors such as tangibility, reliability, responsiveness, assurance, and empathy are evaluated using the SERVQUAL model. Findings aim to provide actionable insights for Klinik Pratama's management to optimize service delivery, ensuring patient satisfaction and fostering loyalty. This study contributes to academic discourse on healthcare management while offering practical recommendations for enhancing primary healthcare services in a competitive landscape. Patient satisfaction, as emphasized in national health service regulations, serves as a benchmark for service quality and sustainability. The research underscores the importance of a strategic and holistic approach to maintaining and improving healthcare delivery standards.